Displaying curves and surfaces in Unity 3D system - Ho, Calvin Kai Jie (Nanyang Technological University, 2019)
In CZ2003 Computer Graphics, students will learn how to generate curves defined by parametric function x(u), y(u), z(u), polygonal surfaces defined by parametric function x(u,v), y(u,v,), z(u,v) and polygonal surfaces defined by implicit functions f(x,y,z)=0 through the use of Virtual Reality Modelling Language (VRML). FVRML is a function-based extension of VRML and allows for extending VRML with any object’s geometry, graphics appearance and transformations by defining the analytical formulas straight in the VRML code. FVRML runs through BS Contact, a 3D player plug-in on Microsoft Internet Explorer. This affects newer systems which predominately use Chrome or Safari as its web browser since Internet Explorer 11 is not the recommended browser for Windows 10 / Mac machines. Furthermore, BS Contact does not support runtime compilation of code. After a student modifies a VRML file, to view updates of the shape, the student will have to close and re-open the 3D player. Hence using FVRML through BS Contact is no longer a suitable teaching aid for students to learn about computer graphics. This study investigates the platform Unity3D’s ability to create curves, surfaces and solids using parametric functions x(u,v), y(u,v), z(u,v) and implicit functions f(x,y,z)=0. Additionally, a convenient user interface will be developed which accepts user’s inputs and display the shape on the interface. The Unity3D platform will serve as a replacement teaching aid application for the CZ2003 computer graphics course.